Alteration of collagenous protein profile in congestive heart failure secondary to myocardial infarction - Pelouch, Václav; Dixon, Ian M; Sethi, Rajat; Dhalla, Naranjan S (Molecular and cellular biochemistry, 1993)
The rat model of myocardial infarction is characterized by progressive cardiac hypertrophy and failure. Rats with infarcts greater than 30% of the left ventricle exhibited early and moderate stages of heart failure 4 and 8 weeks after the occlusion of the left coronary artery, respectively. As heart failure is usually associated with remodeling of the extracellular matrix, a histological and biochemical study of cardiac collagenous proteins was carried out using failing hearts. Total collagen content in the right ventricle increased at 2, 4, and 8 weeks following occlusion of the left coronary artery whereas such a change in viable left ventricle was seen after 4 and 8 weeks. Total cardiac hydroxyproline concentration was increased in both right and left ventricular samples from the infarcted animals when compared to those of control; this increase was due to elevation of pepsin-insoluble collagen fraction. The myocardial noncollagenous/collagenous protein ratio was decreased in experimental right and left ventricular samples when compared to control samples. These findings suggest that an increase in cross-linking of cardiac collagen as well as disparate synthesis of collagenous and noncollagenous proteins occurs in this model of congestive heart failure.
Keywords: Heart Failure; Myocardial Infarction; Collagen; Animals; Rats, Sprague-Dawley; Male; Solubility; Rats